Workers united? How trade union organizations at the European level form political positions on the freedom of services - Seeliger, Martin; Wagner, Ines (Köln, 2016)
"In the course of European integration, national trade unions in Europe founded the umbrella organization of the European Trade Union Confederation in order to establish common political positions. Drawing on the case of supranational politics of services regulation, this study shows how cleavages within the EU's multi-level system of labor regulation make the development of such positions a difficult task. Whereas most research on cleavages at the supranational level focuses either on party groups or national origin, findings indicate a vertical line of conflict within the multi-level system of European trade unionism."